IMPLEMENTATION OF THE CONCEPT OF RELIGIOUS MODERATION IN PRIVATE ISLAMIC HIGHER EDUCATION (PIHE) - Muhammad Ulinnuha (Penamas, 2022)
This paper discusses the application of Religious Moderation (RM) in Private Islamic Higher Education (PIHE). This research focuses on tracing the level of understanding of the academic community towards the RM concept, its implementation and internalization strategy, and exploring the factors that influence its implementation. This research used a mixed-method, descriptive analysis, and an interdisciplinary approach. The samples comprised 60 PIHE. There was consisted of Kopertais I, II, and IV areas with 153 respondents. The data were collected by questionnaires, interviews, observation, and documentation techniques. The results showed; First, the academic community’s understanding of the RM concept is at a low level. Second, the implementation of RM is at a fairly good level. The strategies used to internalize RM are the insertion into courses, training/workshops/seminars, incorporating RM into the curriculum, and extracurricular activities. Third, the factors that influence the implementation of RM consist of internal and external factors. Among the internal factors are campus leadership support, literacy, campus community participation, budget funds, and availability of infrastructure. Meanwhile, external factors are government support, religious and community leaders, social, economic, and political conditions, the education level of the community around campus, and information and communication technology. The level of support from all factors is classified as lacking and tends to be very lacking. Therefore, it cannot encourage the RM implementation process properly and maximally.